Different Approaches To Studying The Natural-Scientific And Historical-Philosophical Heritage Of The Khorezm Academy Of Ma’mun (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article scientifically analyzes the rich natural science heritage and socio-philosophical views of the scientists of the Khorezm Academy of Ma’mun. The rich scientific research and socio-philosophical views of Abu Raikhan al-Biruni, Abu Nasr ibn Iraq and Abu Ali ibn Sina in the field of exact and philosophical sciences, characteristic of this period, are studied. based on exhaustive sources.